2018
DOI: 10.4103/japtr.japtr_345_18
|View full text |Cite
|
Sign up to set email alerts
|

Value of pathologic Q wave in surface electrocardiography in the prediction of myocardial nonviability: A cardiac magnetic resonance imaging-based study

Abstract: In surface electrocardiography (ECG), Q wave is often considered as a sign of irreversibly scarred myocardium. Cardiac magnetic resonance (CMR) imaging is an accurate mean for the detection of myocardial viability. Herein, we study the predictive value of Q wave in nonviable (scarred) myocardium by CMR study. Retrospective analysis of the ECG and CMR data of 35 coronary artery disease patients was performed. The delayed enhancement CMR protocol was used for the detection of viability. The presence of a patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…They found that pathologic Q wave is 81.25% sensitive and 93.15% specific for predicting non-viable myocardium, taking PET images as the gold standard. The authors found non-viable myocardium in 34/105 (32.38%) patients referred for SPECT (Arjmand et al, 2018). On the other hand, a study by Raza et al reported that pathologic Q wave on ECG is not a good indicator of non-viability.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…They found that pathologic Q wave is 81.25% sensitive and 93.15% specific for predicting non-viable myocardium, taking PET images as the gold standard. The authors found non-viable myocardium in 34/105 (32.38%) patients referred for SPECT (Arjmand et al, 2018). On the other hand, a study by Raza et al reported that pathologic Q wave on ECG is not a good indicator of non-viability.…”
Section: Discussionmentioning
confidence: 94%
“…Left ventricular impairment is the primary cause of mortality in patients with myocardial infarction (MI). Revascularization in these patients may improve prognosis (Chew et al, 2018;Melendo-Viu et al, 2020). Patients with viable myocardium have better outcomes and an increased chance of survival than those with non-viable myocardium (Erthal et al, 2019;Kandolin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Our focus is on the presence of ischemic heart disease using electrocardiogram (ECG) interpretation. Deep Q waves on ECG are usually associated with myocardial scarring, commonly from a myocardial infarction (MI) [ 1 , 2 ]. Their presence can raise concern, especially in patients in dire need of time-sensitive surgery.…”
Section: Introductionmentioning
confidence: 99%